Speech at the 2020 Annual Meetings Plenary - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank, spoke about what the World Bank Group has accomplished since last year’s Annual Meetings, particularly the response to COVID-19 and progress made on debt transparency. The COVID-19 pandemic’s toll has been enormous, and people in the poorest countries are likely to suffer the longest and hardest. In response, the approach at the World Bank Group has been comprehensive, focused on saving lives, protecting the poor and vulnerable, working toward sustainable business growth, and rebuilding in better ways. He touched on the four most urgent aspects of this work: 1) poverty and inequality; 2) human capital; 3) debt burdens; and 4) fostering an inclusive and resilient recovery. The scale of the challenges ahead is staggering. IDA-19’s three-year envelope of USD82 billion will not be nearly enough to meet the needs of the world’s poorest countries at this desperate time. IDA has taken broad and fast action to frontload IDA-19 resources and provide surge financing this year to support the initial efforts to address the economic and health impacts of COVID. A USD25 billion supplemental COVID emergency financing package will avert a “financing cliff” in FY22-23 and make available additional resources to IDA countries to support their recoveries.